Dermoscopy of granuloma faciale: a description of a new finding - Márcio Martins Lobo Jardim; Juliana Uchiyama; Priscila Kakizaki; Neusa Yuriko Sakai Valente (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Granuloma faciale is a rare, chronic dermatologic disorder, which mainly affects the face. Recently, dermoscopy has been demonstrated as an important ancillary tool on the clinical diagnosis of facial dermatoses. We report two cases of granuloma faciale with yellow areas on dermoscopy that was not yet described in the literature, corresponding to abundant hemosiderin on histopathological examination.